2019
DOI: 10.1155/2019/8181507
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis in Patients with Erythema Nodosum Leprosum in the Use of Thalidomide and Systemic Corticosteroid in Reference Service in Belo Horizonte, Minas Gerais

Abstract: Introduction. Erythema nodosum leprosum (ENL) is a type of lepra reaction treated with corticosteroids and thalidomide, but this association increases the risk of deep venous thrombosis (DVT). Objective. To report cases of ENL with DVT in the use of thalidomide/corticosteroid associated. Methodology. The study was conducted between December 2015 and December 2016 at the Eduardo de Menezes Hospital (HEM-FHEMIG). Results. A clinical case series of 16 patients, eight from HEM-FHEMIG and eight from the literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[ 84 ] The combination also increases the risk of associated deep vein thrombosis by nearly 10%. [ 85 ]…”
Section: Risk Factorsmentioning
confidence: 99%
“…[ 84 ] The combination also increases the risk of associated deep vein thrombosis by nearly 10%. [ 85 ]…”
Section: Risk Factorsmentioning
confidence: 99%
“…Porto et al (2019) reported 16 cases of DVT, most of them in men, as in the present sample, so they recommend prophylaxis with AAS 100 mg/day when this drug association is used. 9 In addition to this report, there have been several similar ones, from different countries. 6 , 10 , 11 , 12 …”
Section: Discussionmentioning
confidence: 79%